A27 CHARACTERIZATION OF HCV INFECTED PWID IN THE SETTING OF CLINICAL CARE IN CANADA (CAPICA): FINAL RESULTS. (1st March 2018) - Feld, J; Conway, B; Bruneau, J; Cooper, C; Cox, J; Deshaies, L; Fraser, C; Macphail, G; Powis, J; Steingart, C; Stewart, K; Thomas, R; et al.
Abstract: Background: HCV-related liver disease in people who inject drugs (PWIDs) carries a heavy personal, healthcare and societal burden. Current HCV treatment uptake in PWIDs is low and related to barriers at the individual, provider and healthcare system levels. Aims: Collect data related to demographic, medical and behavioral variables in HCV-infected PWIDs already engaged in care in Canada to help define treatment barriers. Methods: This multicenter observational study used retrospective chart review to collect data on patients receiving care from 12 Canadian centers. Patients with chronic HCV infection (HCV RNA+) and a history of injection drug use (in the previous 12 months) were included; HIV co-infection was excluded. Data were collected from October 2015 to February 2016. Results: Of 423 participants: 74% were male, 65% Caucasian, 12% Aboriginal, with a median age of 42 years. All clinical sites provided multidisciplinary care and 11/12 had harm reduction programs. 33% of patients injected daily and 20% recently shared needles. Most frequent HCV genotypes were 1a (47%) and 3 (29%). When the fibrosis score was known (65% cases), 55% had F0-F1 and 14% had F4. The majority of patients were not yet being treated for HCV (83%). Of the 71 patients who received treatment, 37% (26/71) received IFN-free regimens. In the multivariate analysis, increasing age (OR = 1.10, 95% CI [1.03, 1.08]), not using a needle exchange program (OR = 6.95, 95% CI [1.73, 27.97]), moderate alcohol consumption (males ≤ 15 or females ≤ 10 drinks per week) vs. other (OR = 3.70, 95% CI [2.05, 6.69]) and a recent fibrosis assessment with F4 vs. F0-F3 (OR = 4.91, 95% CI [2.18, 11.09]) were associated with a higher likelihood of receiving treatment. Conclusions: A large number of HCV-infected PWIDs are engaged in care in Canada. Treatment rates are still low and patients are being prioritized for treatment. Barriers to treatment identified in this analysis will help to design targeted interventions for this group. Funding Agencies: Merck Canada Inc.